Development and Validity of Electronic Worksheet Based on POE (Predict-Observe-Explain) to Enhance Students Conceptual Understanding on Measurement Materials - mairesma ires; Ratnawulan (Physics Learning and Education, 2026)
The main problems in physics learning at schools are still low learning outcomes and students’ conceptual understanding, especially on the topic of measurement. One solution to overcome these problems is to develop teaching materials in the form of POE (Predict-Observe-Explain) based E-LKPD. This study aims to describe the characteristics of the E-LKPD and determine its validity, so that it can be used in the learning process. This research is a development research using the Plomp model, which includes three main stages: preliminary research, prototyping phase, and assessment phase. Based on the results, the POE (Predict-Observe-Explain) based E-LKPD on measurement topic has been designed with the following characteristics: (1) the E-LKPD is arranged according to the POE learning model, consisting of activities of predicting, observing & measuring, explaining understood concepts, and evaluation; (2) the E-LKPD is developed using Canva Pro and Heyzine Flipbook; (3) the POE based E-LKPD obtained a validation score of 0.93, categorized as valid in terms of content/material appropriateness, language, presentation, graphic design, application of the POE model, and digital media aspects.